Author Correction: Chemically triggered drug release from an antibody-drug conjugate leads to potent antitumour activity in mice - Raffaella Rossin (Nature Portfolio, 2019)
The original version of this Article omitted the following from the Acknowledgements: ‘This work was supported by the Office of the Assistant Secretary of Defense for Health Affairs, through the Breast Cancer Research Program under Award No. W81XWH-15-1-0692. Opinions, interpretations, conclusions and recommendations are those of the author and are not necessarily endorsed by the Department of Defense’. This error has now been corrected in the PDF and HTML versions of the Article.